Serum Growth Hormone and IGF-I Levels, and Submaximal Exercise at High Altitudes and Sea Level - Pérez Valverde, Angel (1999)
OBJETIVE: To assess serum growth hormone (GH) and insulin-like growth factor I (IGF-I) levels among high altitudes (HA) and sea level (SL) natives, and its variations with exercise. METHODS: 50 young men from Cerro de Pasco (4,340 m) and 40 individuals from Lima (150 m) were evaluated. Each subgroup underwent differentintensity exercise. Pre- and post-exercise hematocrit, hemoglobin, glucose, GH, IGF-I, insulin and glucagon levels were recorded. RESULTS: Baseline GH levels at SL showed no significant differences with those at HA (0,79 ng/mL vs. 0,98 ng/mL; p >0,05), whereas baseline IGF-I levels were higher at SL (299,38 ng/mL vs. 63,71 ng/mL; p <0,01). Among SL natives, there were a significant correlation between baseline GH and IGF-I (r = 0,44) levels. Submaximal exercise results in a significant rise of GH (0,79 to 5,54 ng/mL [r = 0,51] and 0,98 to 8,47 ng/mL [r = 0,51] at HA and SL, respectively) levels. On the other hand, exercise exert no significant variations on insulin, IGF1, glucagon or glucose levels. CONCLUSION: Submaximal exercise at HA and SL could result in high fasting GH levels observed in young adults, but it would not increase IGF-I and glucose levels.